2023
DOI: 10.1007/s11030-023-10686-8
|View full text |Cite
|
Sign up to set email alerts
|

A computational study to identify Sesamol derivatives as NRF2 activator for protection against drug-induced liver injury (DILI)

Abstract: Drug-induced liver injury can be caused by any drugs, their metabolites, or natural products due to the inefficient functioning of drug-metabolizing enzymes, resulting in reactive oxygen species generation and leading to oxidative stress-induced cell death. For protection against oxidative stress, our cell has various defense mechanisms. One of the mechanisms is NRF2 pathway, when activated, protects the cell against oxidative stress. Natural antioxidants such as Sesamol have reported pharmacological activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…In addition, docking studies revealed that the most predominant compounds in this tea, which were, caffeine, catechin, catechin gallate, epicatechin, epigallocatechin, epigallocatechin gallate, epicatechin gallate, gallic acid, and gallocatechin, revealed strong Focusing on their potential to interact with the Nrf-2 pathway, Diniyah and colleagues [200] revealed that catechin, epicatechin, and gallic acid from non-oilseed legumes present high binding affinities with Keap1, a protein that activates the degradation of Nrf-2, and are therefore promising new Nrf2 activators. Similar results were found involving hesperetin, hesperidin, naringenin, naringin, narirutin, neohesperidin, neohesperidin dihydrochalcone, and nobiletin citrus-derived flavonoids [201] and sesamol isolated from Sesamum indicum L. seed oil [183]. Mice treated with 37.5, 75, and 150 mg/kg green tea every 8 h by intragastric administration, which were then sacrificed 4, 12, and 20 h after administration, showed higher levels of antioxidative enzymes and liver phase II enzymes.…”
Section: Antioxidant Capacitysupporting
confidence: 77%
See 2 more Smart Citations
“…In addition, docking studies revealed that the most predominant compounds in this tea, which were, caffeine, catechin, catechin gallate, epicatechin, epigallocatechin, epigallocatechin gallate, epicatechin gallate, gallic acid, and gallocatechin, revealed strong Focusing on their potential to interact with the Nrf-2 pathway, Diniyah and colleagues [200] revealed that catechin, epicatechin, and gallic acid from non-oilseed legumes present high binding affinities with Keap1, a protein that activates the degradation of Nrf-2, and are therefore promising new Nrf2 activators. Similar results were found involving hesperetin, hesperidin, naringenin, naringin, narirutin, neohesperidin, neohesperidin dihydrochalcone, and nobiletin citrus-derived flavonoids [201] and sesamol isolated from Sesamum indicum L. seed oil [183]. Mice treated with 37.5, 75, and 150 mg/kg green tea every 8 h by intragastric administration, which were then sacrificed 4, 12, and 20 h after administration, showed higher levels of antioxidative enzymes and liver phase II enzymes.…”
Section: Antioxidant Capacitysupporting
confidence: 77%
“…This is the major pathway involved in the maintenance of homeostatic responses by raising intracellular defense mechanisms and regulating the heme oxygenase-1 axis, controlling macrophage activation and the NF-κB pathway, and reducing stress oxidative and inflammation [181]. Under quiescent conditions, Kelch-like ECH-associated protein 1 (Keap 1) holds Nrf2 in the cytoplasm, promoting its ubiquitination and subsequent proteolysis; however, under pathology conditions, Nrf2 is released from Keap1 and enters the nucleus, where the transcription of antioxidant enzymes occurs [182][183][184].…”
Section: Antioxidant Capacitymentioning
confidence: 99%
See 1 more Smart Citation
“…The mean values of Rg and SASA were conducted across the simulated trajectories, as presented in Table 5. A slight increase in Rg values observed in protein-ligand conformation compared to reference proteins was noticeable indicating that there was a reduction in their structural compactness, hence hinting that these proteins undergo expansion upon binding with ligands [69]. In contrast, the Rg values of the ligated proteins that were not affected by the ligand were found to be similar to those of the proteins that were not bound to any ligand.…”
Section: Simulation Analysismentioning
confidence: 88%
“…According to Mili et al [69], there is a potential for the compounds attached to the protein receptors to exhibit a slightly reduced level of compactness compared to the reference proteins in their unligated state. The SASA value quantifies the extent of the molecular surface that is in contact with the hydrophobic (solvent) environment [70].…”
Section: Simulation Analysismentioning
confidence: 99%